2007
DOI: 10.1007/s10681-007-9506-3
|View full text |Cite
|
Sign up to set email alerts
|

The overexpression of asparagine synthetase A from E. coli affects the nitrogen status in leaves of lettuce (Lactuca sativa L.) and enhances vegetative growth

Abstract: The asparagine synthetase A (EC 6.3.1.1) of E. coli (AS-A) mainly uses ammonia to produce asparagine, a key nitrogen transporter in plants. The AS-A encoding gene (asnA) was expressed constitutively in lettuce cultivar ‘Cortina’ under the control of pMAC, a chimerical promoter, to induce phenotypical alterations of plant growth and quality as a consequence of nitrogen status changes. Nine fertile\ud transgenic lines harbouring independent T-DNA insertions were recovered. Primary transformants shared new visibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 48 publications
4
26
1
Order By: Relevance
“…Additional determinations showed that in AS-A-overexpressing lines, leaf protein content and dry weight were 1.2-to 1.4-fold and 1.3-fold higher, respectively, than those in wild-type plants (Giannino et al, 2008). Overexpression of this enzyme in other leafy crops needs to be assessed to study a possible positive effect on NUE.…”
Section: Genetic Modifications Involving Transcription Factors and Otmentioning
confidence: 98%
“…Additional determinations showed that in AS-A-overexpressing lines, leaf protein content and dry weight were 1.2-to 1.4-fold and 1.3-fold higher, respectively, than those in wild-type plants (Giannino et al, 2008). Overexpression of this enzyme in other leafy crops needs to be assessed to study a possible positive effect on NUE.…”
Section: Genetic Modifications Involving Transcription Factors and Otmentioning
confidence: 98%
“…and is considered soluble in both acidic and alkaline media. ASN has a high N:C ratio (2:4) and great stability, which make it a more economical substance mainly for N-transport and storage in a wide range of living organisms (Giannino et al, 2008;Yang et al, 2011). This point has been ascertained when growing plants were exposed to conditions of excessive NH 3 , such as higher dose of N-fertilizer, and/or under treatments which impose C-limitations, such as subjection to darkness.…”
Section: Role Of Asparagine In Nodule Functioningmentioning
confidence: 99%
“…The transgenic plants with AS-A had new traits, such as a higher leaf number, wider leaf surface and seed germination, formation and development of leaves, bolting and flowering which occurred earlier than the wild-type [16]. The metabolic profile of the transgenic plants also changed accumulating inulins, a polysaccharide beneficial for human health with industrial and medical uses [17,18].…”
Section: Translation From Microorganism Platforms To Plantsmentioning
confidence: 99%
“…The change in the characteristics of key enzymes of nitrogen metabolism of plants, such as glutamine or asparagine synthetases, could improve NUE. In this regard, although protein engineering techniques were not carried out, it has been shown that Lactuca sativa plants transformed with the gene coding for the asparagine synthetase A from Escherichia coli (AS-A), which has different characteristics to the asparagine synthetase of plants, which exhibit an improved NUE [16].…”
Section: Crop Yield Increase: Photosynthesis Engineering (Rubisco) Nuementioning
confidence: 99%
See 1 more Smart Citation